DEVELOPMENT OF PROBLEM-BASED LEARNING SCIENCE E-MODULE INTEGRATED WITH ETHNOSCIENCE OF PENCAK SILAT TO IMPROVE STUDENTS' SCIENCE PROCESS SKILLS - Tia, Junartiah Artia (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
An abstract is often presented separate from the article, so it must be This study aims to develop a Problem-Based Learning (PBL) e-module integrated with ethnoscience pencak silat to improve students' science process skills in respiratory system material. The development model employed a 4-D model (Define, Design, Develop, Disseminate). The e-module was developed based on the needs analysis results, designed according to the structure and format of digital learning media, and validated by material, media, learning, and language experts. The instrument's validity was analyzed using Aiken's V, with results ranging from 0.84 to 0.91, indicating high validity. The product was tested through limited and medium-scale trials, involving 2–3 teachers and 6–24 students, which resulted in positive responses with average percentages above 87%. The effectiveness test through pretest and posttest in experimental and control classes across three schools showed significant improvements in the experimental class. Data analysis using independent sample t-tests indicated significant differences in posttest scores (p < 0.05). The developed e-module proved to be effective, practical, and valid in enhancing students' science process skills, integrating scientific concepts with local cultural wisdom through pencak silat.